The Impact of Tax Treaties and Repatriation Taxes on FDI Revisited - Christoph Harendt; Daniel Dreßler; Michael Overesch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We revisit the effects of double tax treaties on foreign direct investment. Previous empirical studies provide somewhat counterintuitive results suggesting insignificant or even negative effects of tax treaties. Using a rich firm-level dataset provided by the German Central Bank we analyze the investment impact of double tax treaties and repatriation taxes between more than 3,000 country pairs. Whereas we do not find a significant effect of tax treaties on overall investment, we show that repatriation taxes have an adverse effect on fixed assets and a positive effect on financial assets. The latter supports the assumption that firms defer profit distribution to avoid taxes. Correspondingly, we also find that revenue reserves increase in repatriation taxes.
Keywords: F23; H25; H32; 330